2013
DOI: 10.1093/qjmed/hct200
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate communities: end-of-life care as everyone's responsibility

Abstract: In early 2013, an online survey of over 200 UK palliative care services published in the British Medical Journal found that most of these services were prioritizing 'community engagement' initiatives, most commonly adopting a 'compassionate community' model. Later this same year, a report released by the National Council for Palliative Care and the charity Murray Hall Community Trust, described the increasing uptake of compassionate communities by palliative care services in England. This review examines this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
191
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(224 citation statements)
references
References 3 publications
1
191
0
15
Order By: Relevance
“…55 This area of activity is often called health promoting palliative care, a concept that originated in Australia from the work of Kellehear. [56][57][58][59][60] It is in line with the framework presented by Ottawa Charter on Health Promotion. 61 Another related term is ''the public health approach to palliative care,'' 59,62 with an international network of partners dedicated to promotion of this.…”
Section: Palliative Care Campaigns S-31supporting
confidence: 72%
“…55 This area of activity is often called health promoting palliative care, a concept that originated in Australia from the work of Kellehear. [56][57][58][59][60] It is in line with the framework presented by Ottawa Charter on Health Promotion. 61 Another related term is ''the public health approach to palliative care,'' 59,62 with an international network of partners dedicated to promotion of this.…”
Section: Palliative Care Campaigns S-31supporting
confidence: 72%
“…There are advantages associated with tailoring a service to an individual as well as to a community or group, as shown by user satisfaction [14] and wellbeing [1617]. Examples of actions that are helpful in pursuing this aim include defining a clear target group [18], creating connections between different sectors [19], and between members of a community and practitioners [2021].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two-way communication with family, informal carers and the broader community, is an important requisite of the growing ''compassionate community'' approach to palliative care. 33 Indeed, while we want to improve EOL symptom assessment in acute hospitals, it is just as important to avoid unnecessary hospitalization at EOL if the person with dementia had indicated that this is their wish.…”
Section: Discussionmentioning
confidence: 99%